Development of a colloidal gold-based lateral flow dipstick immunoassay for rapid qualitative and semi-quantitative analysis of artesunate and dihydroartemisinin - He, Lishan (BioMed Central, 2014)
BACKGROUND: Artemisinin-based combination therapy (ACT) plays an indispensable role in malaria control and elimination. However, the circulation of counterfeit, substandard drugs has greatly threatened malaria elimination campaigns. Most methods for the analysis of artemisinin and its derivatives require expensive equipment and sophisticated instrumentation. A convenient, easy-to-use diagnostic device for rapid evaluation of the quality of artemisinin drugs at the point-of-care is still lacking. In this study a lateral flow dipstick immunoassay was developed for qualitative and semi-quantitative analysis of artesunate (ATS) and dihydroartemisinin (DHA) in anti-malarial drugs. METHODS: This assay was based on a monoclonal antibody (mAb) raised against ATS. ATS-bovine serum albumin and goat anti-mouse IgG, used as the test capture reagent and the control capture reagent, were coated on the nitrocellulose membrane to form the test line and control line, respectively. The conjugate pad was saturated with the gold-labelled anti-ATS mAb. RESULTS: The indicator range of the dipsticks, defined as lowest concentration of the target analytes between which the test line was not visible, were 100-200 and 200-500 ng mL(-1) for ATS and DHA, respectively. No competitive inhibition was observed up to 5,000 ng mL(-1) of quinine, chloroquine diphosphate salt, primaquine phosphate, pyrimethamine, lumefantrine, amodiaquine, piperaquine tetraphosphate tetrahydrate or pyronaridine tetraphosphate. Semi-quantitative analysis of ATS and DHA in commercial drugs and raw drug materials with the dipsticks produced result agreeable with those determined by high performance liquid chromatography (HPLC). Storage test showed that the indicator range for artemisinins remained unchanged after a week at 37°C and increased four-folds after six months of storage at 4°C or ambient temperature. CONCLUSIONS: The new selected mAb 3D(8)2G(7) with high avidity and broad cross reactivity for artemisinins was used to develop and optimize a dipstick immunoassay for qualitative and semi-quantitative analysis of ATS and DHA in anti-malarial drugs. The semi-quantitative analysis of ATS and DHA in commercial drugs and raw drug materials, and the specificity test of the artemisinin-related drugs both proved the accurate performance of the developed dipsticks for semi-quantitation of ACT samples. The dipstick may be used as a point-of-care device for identifying substandard and counterfeit ATS- and DHA-containing anti-malarial drugs.